The New Summer Break. - Weiss, Michael J. (American Demographics, 2001)
Children of every socioeconomic and ethnic background now boast nonstop scheduling all summer long, which is a trend fueled by the growing numbers and financial power of Generation Y, the 71 million people born between 1977 and 1994. Instead of playing sandlot baseball or dropping a fishing line into a creek, the current generation of American children is more likely to spend the summer attending a series of camps and classes that involve traveling overseas, reconstructing dilapidated housing in inner cities, and volunteering for internships in research areas. Recognizing the potential power of Generation Y members, a group of camp directors, travel agents, and corporate executives has started to target this burgeoning and lucrative market. Details of this group's efforts are provided.